FATORES ASSOCIADOS AO TEMPO DE SOBREVIDA DE CRIANÇAS E ADOLESCENTES PÓS TRANSPLANTE DE SANGUE DE CORDÃO UMBILICAL - PETTERLE, Ricardo Rasmussen; GAUTÉRIO, Tairine Lippi; JANNINI, Flávia da Nobrega; LONGO, Natália Dettoni; ULBRICH, Anderson Zampier; SHIMAKURA, Silvia Emiko; NICHELE, Samantha; BONFIM, Carmem Maria Sales (Brazilian Journal of Biometrics, 2018)
Umbilical cord blood (UCB) is an alternative source for transplantation of hematopoietic stem cells (HSC). The SCU has simple logistics and clinical advantages such as the possibility of performing transplants with some incompatibilities, increasing the chances of nding donors. In this context, the objective of this study was to analyze the viral, bacterial and fungal infections among other factors relate to long-term survival of children and teens after cord blood transplantation. Data were collect from January 1996 to October 2012 from the bone marrow transplant service of the Hospital de Clinicas, Federal University of Parana. Data analysis included Cox Proportional Hazards Model and log-normal fragility. The results of the both models showed similar results and pointed to the same directions. The female children with neurological complications, bacterial and viral infections, and viral infection were more prone to death after cord blood transplantation.